Comparative Study of Urinary Calcium Levels in Women With Preeclampsia Compared to Normotensive Pregnant Women in Lagos, Nigeria - Aloy Okechukwu Ugwu; Nwabueze Gabriel Osuji; Christian C. Makwe; Kehinde S Okunade; Sunday Isaac Omisakin; Achonu Chinemeri U; Odoh Elizabeth Uchechukwu; Daniel Bukunmi Fadeyi (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Background: Preeclampsia is currently defined as multisystem progressive disorder characterized by the new onset of hypertension and proteinuria or the new onset of hypertension and significant end-organ dysfunction with or without proteinuria, typically presenting in the second half of pregnancy (after twenty weeks) or postpartum in a previously normotensive woman without proteinuria and resolves within six weeks postpartum Despite numerous theories, the aetiology of preeclampsia has not been fully elucidated. It is postulated that the rise in blood pressure is a manifestation of more than one patho-physiological condition. One of these conditions is related to abnormal renal function and probably impairment of urinary calcium excretion. Objective: This study compared urinary calcium levels in women diagnosed with pre-eclampsia and normotensive pregnant women at the Lagos University Teaching Hospital, Lagos, Nigeria. Methods: This was an analytical cross-sectional study that enrolled 100 preeclamptic pregnant women and their matched normotensive counterparts carried out at the antenatal clinic and the labour ward of the Lagos University Teaching Hospital. The urinary calcium level was analysed with spot urine using Orthocresolphthaleincomplexone (CPC) method (Fortress Diagnostics Limited United Kingdom, Product code BXC0291A). Results: The mean urinary calcium levels in women with preeclampsia (2.44±1.45mmol/L) was significantly lower than that of normotensive pregnant women (4.43±1.84mmol/L) (p < 0.001). However, there was no significant difference in the mean urinary calcium levels in participants with mild preeclampsia (2.49±1.54mmol/l) compared to those with severe preeclampsia (2.42±1.42mmol/L), (p = 1.000). Conclusion: The study revealed a significantly lower level of urinary calcium in women with preeclampsia compared with that of their healthy normotensive counterparts. However, the study did not reveal any significant difference in the urinary calcium level in participants with mild and severe preeclampsia.